2021
DOI: 10.1515/pp-2020-0141
|View full text |Cite
|
Sign up to set email alerts
|

Is the blood of a surgeon performing HIPEC contaminated by irinotecan, its major metabolites and platinum compounds?

Abstract: Objectives Hyperthermic intraperitoneal chemotherapy (HIPEC) is a beneficial surgical technique for patients, but the surgeons are being exposed to cytotoxic drugs. Few biomonitoring studies were led on blood samples in the context of HIPEC. This study aimed to evaluate the surgeon’s plasmatic and red blood cell (RBC) contamination by irinotecan, two of its major metabolites and platinum compounds. Methods HIPEC procedures pe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
7
0
1

Year Published

2021
2021
2023
2023

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 7 publications
(9 citation statements)
references
References 25 publications
0
7
0
1
Order By: Relevance
“…Nevertheless, environmental contamination could be detected in various locations in the operating rooms, including gloves, hands, devices, and floor. In a more recent study, Saint-Lorant et al [ 28 ] demonstrated a Pt contamination in 36% (7 out of 19) of plasma samples collected from a French surgeon engaged in 17 HIPEC procedures for a period of 3 years.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…Nevertheless, environmental contamination could be detected in various locations in the operating rooms, including gloves, hands, devices, and floor. In a more recent study, Saint-Lorant et al [ 28 ] demonstrated a Pt contamination in 36% (7 out of 19) of plasma samples collected from a French surgeon engaged in 17 HIPEC procedures for a period of 3 years.…”
Section: Resultsmentioning
confidence: 99%
“…When the IRT contamination was investigated in a surgeon exposed during HIPEC procedures [ 28 ], despite collective and PPE, 79% and 63% of plasma and red blood cell samples were contaminated, both soon after HIPEC procedures, as well as following a period of inactivity.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Bu nedenle bu tekniğin kullanımı söz konusu ise teması önleyecek koruyucu ekipman kullanımının gerekli olduğunu bildirmişlerdir (17). Ancak Lorent ve ark (2021) açık teknik HİPEK uygulamasında özel kişisel koruyucu ekipman (PVC su geçirmez botlar, cerrahi önlük, FFP3 maske ve 2 çift neopren 1 çift lateks cerrahi eldiven) kullanımına rağmen cerrahların kan örneklerinde irinotekan ve platin saptamıştır (18). Açık teknikte cerrahi ekibin kemoterapötik ajanlar ile dermal yoldan maruziyet riskinin oldukça yüksek olduğu sonucuna varılmıştır.…”
Section: Kemoterapötik Ajanlarla İlişkili Risklerunclassified
“…Therefore, even though the OR and CU are considered to be quite different from several points of view, blood contamination by ADs has been detected in caregivers attached to both locations. 2729…”
Section: Introductionmentioning
confidence: 99%